Patient Priority-Directed Decision Making and Care for Older Adults with Multiple Chronic Conditions - Tinetti, Mary E; Esterson, Jessica; Ferris, Rosie; Posner, Philip; Blaum, Caroline S (Clinics in geriatric medicine, 2016)
Older adults with multiple conditions receive care that is often fragmented, burdensome, and of unclear benefit. An advisory group of patients, caregivers, clinicians, health system engineers, health care system leaders, payers, and others identified three modifiable contributors to this fragmented, burdensome care: decision making and care focused on diseases, not patients; inadequate delineation of roles and responsibilities and accountability among clinicians; and lack of attention to what matters to patients and caregivers (ie, their health outcome goals and care preferences). The advisory group identified patient priority-directed care as a feasible, sustainable approach to addressing these modifiable factors.